ISOLATION AND CHARACTERIZATION OF PHOSPHATE SOLUBILIZING BACTERIA FROM AGRICULTURAL SOILS OF AMHARA AND AFAR REGIONS ETHIOPIA. - Bogale Damtew, Meera Indracanti, Katherine G. Menon, Priyadarsini B, Tekeba Sisay, Nega Berhane (Chelonian Research Foundation, 2023)
Phosphorus (P) is one of the essential macro-elements that increase soil fertility and the growth and development of plants. However, phosphorus's complex occurrence makes it soluble and accessible. The objective of the present study was to isolate, characterize, and assess the phosphate solubilizing capacity of bacteria from agricultural soil samples of the Dupti wereda of Afar region and Deskua kebele, Kimir-Dingay district in the south Gondar Zone. This study was conducted at the Cellular and Microbial Laboratory, Institute of Biotechnology, University of Gondar, Gondar, Ethiopia. Isolated phosphoramide solubilizing bacteria were characterized morphologically and biochemically. A total of ten phosphate-solubilizing bacteria were isolated and were coded as DU1, DU2, DU3, DU4, DU5, DU6, DE1, DE2, DE3, and DE4. Out of ten isolates, eight were gram-positive, and two were gram-negative. The phosphate solubilization efficiency of isolates was identified based on the formation of a clear zone around PVK media and liquid broth containing calcium triphosphate. Among the isolates DU5, DE1, DE2 and DU1 have been observed to be the maximum solubility index. When the solubilization efficiency of isolates was observed in liquid broth, the highest P release was recorded by isolates DE1 followed by DU5, DE2 and DE4. Based on solubilization efficiency and stress-tolerant capability, only six isolates were selected for pot experiments in the faba bean and wheat varieties. Isolate PSB DU5 showed the best effect on shoot length (71.66 ±15.27), root length (12.66 ±3.7), leaf number (39±4.35), nod number (13.3±0.57). Isolates PSB DU1, PSB DE1, and DE2 showed second and third-best effects on the shoot length of Dosha faba bean growth, respectively. Similarly, PSB DU3 significantly increased root length. When the impact of the isolates is compared based on their shoot length of the inoculated Eliodoro wheat variety, isolates DU1 and DU5 were observed to be the most effective in enhancing plant growth for shoot length. Keywords: Phosphorus, phosphate solubilizing bacteria, solubility index.